Supervisi Kolaboratif dalam Meningkatkan Kemampuan Profesional Guru di SMA Negeri Kota Bandung - Hadiansyah, Chairil Fajar; Az Zahro, Fatimah; Wahidin, Wahidin; Ismail, Achmad Taufik (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2025)
This study aims to describe how collaborative supervision is implemented by the school principal and to examine its contribution to teachers’ professional competence at one of SMA Negeri in Bandung City. Employing a qualitative case study design, purposive sampling involved the principal, a supervising school inspector, the vice principal for curriculum, and six subject teachers. Data were collected through semi-structured interviews, limited participatory observations, and document analysis; data were analyzed interactively using iterative reduction, display, and conclusion/verification procedures. Findings indicate that collaborative supervision unfolds in three interrelated phases: (1) planning (needs identification, negotiated focus, and pre-observation conferences); (2) implementation (clinical classroom observation and dialogic feedback); and (3) follow-up (joint reflection, instructional coaching, and integration with a professional learning community/PLC). Contributions include measurable improvements in teachers’ competencies regarding lesson planning, active and innovative instruction, meaningful formative assessment, and strengthened professional reflection. Key enabling factors are the principal’s instructional leadership, a collaborative school culture, and teachers’ readiness to learn; major challenges include time constraints and administrative load, residual evaluative perceptions of supervision, and uneven coaching skills among supervisors. Practical implications call for strengthening principals’/supervisors’ coaching capacity, safeguarding time for reflective practice through scheduling, and systematically integrating supervision with PLC and lesson study for sustained professional growth.